2004
DOI: 10.1111/j.1365-2273.2004.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional challenges in head and neck cancer

Abstract: In head and neck cancer patients malnutrition impacts on quality of life, complications of therapy and also prognosis, in part via altered immunity. Dysphagia assessment is extremely valuable but more work is needed to optimize the rehabilitation of the incompetent swallow in this particular patient group. Proper nutritional assessment is mandatory pre-/peri-/post-treatment. The range and palatability of nutritional supplements has greatly increased over the past few years. Many of the early problems of percut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 56 publications
0
20
0
1
Order By: Relevance
“…The median survival was 17 days (95% confidence interval [CI; [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]). The average of serum CRP level was 6.12± 5.35 (mg/dl).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median survival was 17 days (95% confidence interval [CI; [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]). The average of serum CRP level was 6.12± 5.35 (mg/dl).…”
Section: Resultsmentioning
confidence: 99%
“…In our results, CRP is inversely correlated with hemoglobin or albumin, which reflected malnutrition status. It can be hypothesized that elevated CRP levels increase mortality through malnutrition because malnutrition is associated with impaired immunity [21].…”
Section: Discussionmentioning
confidence: 99%
“…percentage of weight loss, percentage of ideal body weight, nutrition index, serum albumin, total lymphocyte count, and body fat (20-67% range of abnormal scores), the one which has emerged as the most powerful predictor of major postoperative complications is a weight loss of >10% in the M. R. Chasen (*) : R. Bhargava 6 months before surgery [12]. An early prospective study of 114 patients showed that 38% with a nutritional deficit had a 2-year survival of only 7.5% compared with over 57% in the remainder of the cohort [13]. This manuscript will review both altered physiology in patients with head and neck cancers and the clinical consequences of those changes.…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, the challenge ahead is to gain a better understanding of the nature of the dysphagia associated with new treatment modalities and the impact of this treatment modality on nutritional outcomes 10 .…”
Section: Introductionmentioning
confidence: 99%